2014
DOI: 10.1007/s00223-014-9894-z
|View full text |Cite
|
Sign up to set email alerts
|

Lean Mass, Muscle Strength and Gene Expression in Community Dwelling Older Men: Findings from the Hertfordshire Sarcopenia Study (HSS)

Abstract: Sarcopenia is associated with adverse health outcomes. This study investigated whether skeletal muscle gene expression was associated with lean mass and grip strength in community-dwelling older men. Utilising a cross-sectional study design, lean muscle mass and grip strength were measured in 88 men aged 68-76 years. Expression profiles of 44 genes implicated in the cellular regulation of skeletal muscle were determined. Serum was analysed for circulating cytokines TNF (tumour necrosis factor), IL-6 (interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 47 publications
0
57
0
1
Order By: Relevance
“…Although observational human studies support a link between vitamin D status and Vitamin D deficiency is also reported to be associated with the loss of skeletal muscle mass and strength especially in the elderly [32,33], but no intervention trials have been performed to determine the impact of vitamin D supplementation on body composition in humans. The present study found that vitamin D sufficiency preserved lean body mass that was lower in vitamin D deficient rats and intermediate with excessive vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 96%
“…Although observational human studies support a link between vitamin D status and Vitamin D deficiency is also reported to be associated with the loss of skeletal muscle mass and strength especially in the elderly [32,33], but no intervention trials have been performed to determine the impact of vitamin D supplementation on body composition in humans. The present study found that vitamin D sufficiency preserved lean body mass that was lower in vitamin D deficient rats and intermediate with excessive vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study suggested that myostatin, which is one of the factors in the ubiquitin proteasome system, might be a potential mechanism of this triangle association. First, higher serum myostatin is associated with lower HGS [21], and lower myostatin is associated with higher HGS [22].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is also associated with decreased muscle regenerative capacity that can further exacerbate loss of function. Together, these changes lead to increased risk of falling, loss of physical independence, and increased morbidity and mortality (Landi et al, 2012; Patel et al, 2014; Xue, Walston, Fried, & Beamer, 2011). Although sarcopenia is influenced by intrinsic changes in muscle (Sousa‐Victor et al, 2014) and by extrinsic factors from other systems (Carlson & Faulkner, 1989; Fry et al, 2015), the specific mechanisms that drive sarcopenia are largely unknown.…”
Section: Introductionmentioning
confidence: 99%